Polarisation applications in remote sensing - Cloude, Shane (Oxford : Oxford University Press, 2010)
This is a monograph concerning the scattering of electromagnetic waves from surfaces to generate information for the purposes of remote sensing. It combines a treatment of two important new ideas, namely information from the orientation or polarisation of the wave and how it can be combined with interferometry.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Polarimetric remote sensing; Radio waves -- Polarization; Interferometry; Electromagnetic waves -- Scattering